2007
DOI: 10.1177/1934578x0700200806
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Cissus quadrangularis L. Derived Components on Lipase, Amylase and α-Glucosidase Activity in vitro

Abstract: The stems of Cissus quadrangularis L (Vitaceae) have been consumed for centuries throughout Asia and Africa as a culinary vegetable. The aqueous extract of C. quadrangularis stems and leaves contains flavonoids and stilbenes, which inhibit lipase, amylase and α-glucosidase and, therefore, might be, at least in part, related to the claimed anti-obesity activity of the plant. The enzyme inhibition activity is outlined of a novel flavonoid (3- O-α-L-rhamnopyranosylkaempferol) (2) and stilbene (3-(4-hydroxybenzyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…For bone fractures and obesity/overweight management, this is the first meta-analysis summarizing the clinical benefits of Cissus for these indications. However, benefits of Cissus for these indications and other bone and joint diseases were demonstrated in several preclinical studies (Panthong et al 2007, Sharma and Patni 2007, Sharp et al 2007, Jiji et al 2009, Chidambaram and Carani 2010, Chaudhari et al 2013, Lekshmi et al 2014. The proposed mechanisms of Cissus extract for bone and joint diseases are enhancing bone growth and healing, analgesic, antiinflammatory, and anti-osteoporotic activities (Panthong et al 2007, Sharma and Patni 2007, Potu et al 2010, AbdJalil et al 2012, Aswar et al 2012, Banu et al 2012, Gupta et al 2012, Sirasanagandla et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bone fractures and obesity/overweight management, this is the first meta-analysis summarizing the clinical benefits of Cissus for these indications. However, benefits of Cissus for these indications and other bone and joint diseases were demonstrated in several preclinical studies (Panthong et al 2007, Sharma and Patni 2007, Sharp et al 2007, Jiji et al 2009, Chidambaram and Carani 2010, Chaudhari et al 2013, Lekshmi et al 2014. The proposed mechanisms of Cissus extract for bone and joint diseases are enhancing bone growth and healing, analgesic, antiinflammatory, and anti-osteoporotic activities (Panthong et al 2007, Sharma and Patni 2007, Potu et al 2010, AbdJalil et al 2012, Aswar et al 2012, Banu et al 2012, Gupta et al 2012, Sirasanagandla et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanisms of Cissus extract for bone and joint diseases are enhancing bone growth and healing, analgesic, antiinflammatory, and anti-osteoporotic activities (Panthong et al 2007, Sharma and Patni 2007, Potu et al 2010, AbdJalil et al 2012, Aswar et al 2012, Banu et al 2012, Gupta et al 2012, Sirasanagandla et al 2014. Whereas, inhibition of certain enzymes as alpha amylase, glucosidase and lipase, anti-hyperglycemic, anti-lipidemic activities, and tissue protective effects associated with fatty lipid and carbohydrate metabolism are the mechanisms for obesity/overweight management (Sharp et al 2007, Jiji et al 2009, Chidambaram and Carani 2010, Chaudhari et al 2013, Lekshmi et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The stem and leaf of the Cissus quadrangularis are used in food preparation in India. Numerous studies demonstrated that methanolic and petroleum ether extract of the whole plant are used in treating osteoporosis and fracture (Deka et al, 1994;Shirwaikar et al, 2003;Sharpa et al, 2007). It possesses antioxidant (Jainu and Shyamaladevi, 2005), antiinflammatory, antibacterial (Kashikar and George, 2006;Thakur et al, 2009), antiviral (Balasubramaniana et al, 2010), and antiulcerogenic Shyamaladevi, 2004, 2006;Jainu et al, 2010) properties.…”
Section: Introductionmentioning
confidence: 95%
“…Cissus quadrangularis (CQ), a succulent vine native to West Africa and Southeast Asia, has been used in traditional African and Ayurvedic medicine for more than a century. Although some studies [ 7 - 10 ] have examined other uses of CQ, its role in fighting obesity and symptoms of metabolic syndrome has attracted interest in other parts of the world [ 11 - 14 ]. The unique chemical constituents of CQ–novel flavonoids and indanes, as well as phytosterols and keto-steroids–have shown promise as powerful and efficient antioxidants [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%